Pengaturan Kewenangan Pembuatan Akta Pertanahan Antara Notaris Dan Pejabat Pembuat Akta Tanah - Adi Rahayu (Recital Review, 2019)
This article discusses the regulation-making authority between the notary and Pejabat Pembuat Akta Tanah (PPAT). In making the land deed, notary authority derived from attribution attached to the profession of notary, whereas PPAT authority derived from a delegate or delegation of authority from the competent authority, in this case Badan Pertanahan Nasional. Deed of land made by or in the presence of a notary deed is authentic and has the strength of evidence is perfect, while issued PPAT ineligible authentic deed and only has the strength of evidence deed under hand